2010
DOI: 10.1093/pcp/pcq020
|View full text |Cite
|
Sign up to set email alerts
|

The PsbK Subunit is Required for the Stable Assembly and Stability of Other Small Subunits in the PSII complex in the Thermophilic Cyanobacterium Thermosynechococcus elongatus BP-1

Abstract: PsbK is a small membrane protein of the PSII core complex and is highly conserved from cyanobacteria to plants. Here, we studied its role in the thermophilic cyanobacterium, Thermosynechococcus elongatus BP-1, by focusing on a psbK disruptant with hexahistidine-tagged CP47. The psbK disruptant showed photoautotrophic growth comparable with that of the wild type under a wide range of light conditions. The mutant PSII complex retained the oxygen-evolving activity with a unique modification of the acceptor Q(B) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
1
16
0
1
Order By: Relevance
“…2 and 3). Recently, it was shown that the removal of PsbK, which is close to PsbJ, in PsbA1-PSII resulted in the complete loss of Psb30 and partial loss of PsbZ (49). In the present work it is shown that the removal of PsbJ has no effect on the PsbK content, and maybe as a consequence, it has no effect on the content of Psb30 and PsbZ.…”
Section: Table 2 Assignment Observed and Calculated Molecular Massesupporting
confidence: 44%
“…2 and 3). Recently, it was shown that the removal of PsbK, which is close to PsbJ, in PsbA1-PSII resulted in the complete loss of Psb30 and partial loss of PsbZ (49). In the present work it is shown that the removal of PsbJ has no effect on the PsbK content, and maybe as a consequence, it has no effect on the content of Psb30 and PsbZ.…”
Section: Table 2 Assignment Observed and Calculated Molecular Massesupporting
confidence: 44%
“…The oxygen-evolving PSII core complexes were purified from cells of the T. elongatus 47-H strain (63), in which a (His) 6 -tag was genetically attached to the carboxyl terminus of the CP47 subunit, using Ni 2+ -affinity column chromatography as described previously (64). The O 2 evolution activity of PSII core complexes was 2,500-2,800 μmol O 2 ·(mg Chl) −1 ·h −1 .…”
Section: Methodsmentioning
confidence: 99%
“…S3, left). A role for PsbZ and Psb30 in binding Psb27 seems equally unlikely, given that the absence of PsbK in T. elongatus also destabilizes binding of PsbZ and Ycf12/Psb30 to CP43 (Iwai et al, 2010).…”
Section: Location Of Psb27 Within Psiimentioning
confidence: 99%